Frequency of Common Clinical Presentation in patients with Molar Pregnancy in Gomal Medical College, Dera Ismail Khan, Pakistan - Najma Bibi, Irum Batool Hashmi, Sobia Ahmad, Neelam Mehsood, Naseem Saba, Shazia Bibi, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hydatidiform mole, frequently referred to as molar pregnancy, represents the most prevalent and benign variant of gestational trophoblastic disease. The occurrence rate of molar pregnancy exhibits significant geographical variability, ranging from one in every one hundred and fifty live births in Southeast Asia to one in every one thousand and five hundred pregnancies in the United States. This study identifies the most commonly presenting clinical features of molar pregnancy. The results will help clinicians in early diagnosing of molar pregnancy and prompt management. Material and Method: The study was carried out in the Obstetrics and Gynecology Unit at MTI Gomal, located in DI Khan. The timeframe allocated for this study spanned one year, commencing on the 14th of June 2022 and concluding on the 13th of December 2022. Sample Size was 139 patients that were diagnosed and managed as cases of Molar pregnancy. Sampling Technique was convenience sampling or Non probability purposive and study design was descriptive study Results: Within the scope of this research, a total of 139 patients diagnosed with molar pregnancy were meticulously observed in the obstetrics and gynecology department. Various clinical outcomes were identified and followed and hence put to further management. In these 139 patients the age range was from 18-48 years. It was found that the majority of the patients were complete moles. Abnormal vaginal bleeding emerged as the predominant clinical manifestation of molar pregnancy, being documented in 62 (44.6%) of the patients evaluated. Conclusion: Targeting these various clinical outcomes and close surveillance will then help in improving mortality and morbidity from molar disease. Keywords: Molar Pregnancy, Abnormal vaginal bleeding, Hyperemesis, Theca Lutein cysts, Hyperthyroidism.